The determinants of firm performance: unions, works councils, and employee involvement/high performance work practices - Addison, John T. (Bonn, 2005)
"Drawing on evidence from the United States and Germany, this paper offers a survey of the effects of worker representation (in unions and works councils) and innovative work practices on firm performance. The focus is on the growing links between these two historically separate literatures. The interaction between worker representation and high performance work practices provides a practical means of peering inside the black box of collective voice, even if there is as yet no well-determined hierarchy for productivity performance and certainly no blue-print for the future of unions."